OASes and STING: Adaptive Evolution in Concert. (9th March 2015) - Mozzi, Alessandra; Pontremoli, Chiara; Forni, Diego; Clerici, Mario; Pozzoli, Uberto; Bresolin, Nereo; Cagliani, Rachele; Sironi, Manuela
Abstract : OAS (2′–5′-oligoadenylate synthases) proteins and cyclic GMP–AMP synthase (cGAS, gene symbol: MB21D1 ) patrol the cytoplasm for the presence of foreign nucleic acids. Upon binding to double-stranded RNA or double-stranded DNA, OAS proteins and cGAS produce nucleotide second messengers to activate RNase L and STING (stimulator of interferon genes, gene symbol: TMEM173 ), respectively; this leads to the initiation of antiviral responses. We analyzed the evolutionary history of the MB21D1–TMEM173 and OAS–RNASEL axes in primates and bats and found evidence of widespread positive selection in both orders. In TMEM173, residue 230, a major determinant of response to natural ligands and to mimetic drugs (e.g., DMXAA), was positively selected in Primates and Chiroptera. In both orders, selection also targeted an α-helix/loop element in RNase L that modulates the enzyme preference for single-stranded RNA versus stem loops. Analysis of positively selected sites in OAS1, OAS2, and MB21D1 revealed parallel evolution, with the corresponding residues being selected in different genes. As this cannot result from gene conversion, these data suggest that selective pressure acting on OAS and MB21D1 genes is related to nucleic acid recognition and to the specific mechanism of enzyme activation, which requires a conformational change. Finally, a population genetics-phylogenetics analysis in humans, chimpanzees, and gorillas detected several positively selected sites in most genes. Data herein shed light into species-specific differences in infection susceptibility and in response to synthetic compounds, with relevance for the design of synthetic compounds as vaccine adjuvants.